"Those who can't hear must feel": Confronting racism, privilege, and self with pre-service teachers. Issue 3 (2nd July 2020) - Shannon-Baker, Peggy
ABSTRACT: Teacher education courses on multicultural education, social justice, and international cross-cultural experiences have been used to increase pre-service teachers' (PST) cross-cultural skills and awareness. Critical researchers have shown that without intentional facilitation and program design, PSTs hold onto (if not become more entrenched in) biases and stereotypes. Building on that literature, this article shares the author's practices designed to help PSTs go "outside of [their] bubble" to actively engage with racism, privilege, and the self while participating in international programs. These practices emphasize the importance of emotional and uncomfortable experiences. The article shares the importance of learning about racism and privilege at home before travel, using multi-modal reflections and dialogue, and teacher educators and program leaders similarly engaging in critical self-reflection. Specific activities and stances are shared to encourage their implementation in other programs, as well as areas to improve how international programs engage PSTs in critical self-reflection.